2020
DOI: 10.1142/s0192415x20500913
|View full text |Cite
|
Sign up to set email alerts
|

Geniposide Enhances Macrophage Autophagy through Downregulation of TREM2 in Atherosclerosis

Abstract: Macrophage autophagy defect is closely related to the progression of atherosclerosis (AS) and is regulated by the triggering receptor expressed on myeloid cell 2 (TREM2). TREM2 is a key factor in the development of Alzheimer’s disease (AD), the deficiency of which leads to anomalous autophagy in microglia. However, the role of TREM2 in the autophagy of plaque macrophages is still unclear. Geniposide (GP) can inhibit AS progression and enhance macrophage autophagy, although the underlying mechanisms remain unkn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 33 publications
0
12
0
1
Order By: Relevance
“…GP and NR1 are active compounds extracted from G. jasminoides Ellis and notoginseng, respectively. It has been proven that GP or NR used alone can alleviate the occurrence and development of AS ( Jia et al, 2014 ; Xu et al, 2020 ). GN combination is a patented and approved TCM drug for the prevention and treatment of AS, whose effect is better than that of GP or NR used alone.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…GP and NR1 are active compounds extracted from G. jasminoides Ellis and notoginseng, respectively. It has been proven that GP or NR used alone can alleviate the occurrence and development of AS ( Jia et al, 2014 ; Xu et al, 2020 ). GN combination is a patented and approved TCM drug for the prevention and treatment of AS, whose effect is better than that of GP or NR used alone.…”
Section: Discussionmentioning
confidence: 99%
“…ApoE −/− mice were fed an HFD for 12 weeks to establish the AS model, while the Con group mice were fed a normal diet. After 12 weeks, the GP, NR, and GN groups were respectively given geniposide (50 mg kg −1 ), Panax notoginseng R1 (50 mg kg −1 ) and geniposide + notoginsenoside R1 (50 + 50 mg kg −1 ) by intraperitoneal injection for 12 weeks ( Xiao et al, 2018 ; Xu et al, 2020 ), and the remaining control mice were treated with the same volume of normal saline. After the last administration, the body weight and fasting blood glucose of all mice were detected.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Decreases the size of atherosclerotic plaques (Xu Y. L. et al, 2020) formation characterized by LC3 production and p62 degradation and suppress palmitic acid-induced ROS to attenuate endothelial oxidative injury in HUVECs (Zhou et al, 2019).…”
Section: Geniposide Mtor Inhibition Antiinflammationmentioning
confidence: 99%
“…Previous study demonstrated that geniposide decreased the size of atherosclerotic plaques, inhibited the progression of atherosclerosis in high fat diet-fed ApoE −/− mice. The potential mechanism may contribute to the reinforce of macrophage autophagy by inhibiting the triggering receptor expressed on myeloid cell 2 (TREM2)/mTOR signaling (Xu Y. L. et al, 2020).…”
Section: Natural Productsmentioning
confidence: 99%